Analysis of Embryology and Reproductive Textbook Needs of Integrated Animal Research Results of Development of Mice Embryos by Providing DEET (Diethyltoluamide) - Sulikan, Sulikan; Kusmawati, Wiwik; Anugraini, Asri Putri; Hindun, Nurmala; Irwansyah, Irwansyah (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to analyze the needs of the Embryology and Animal Reproduction textbook integrated with the results of research on developing mouse embryos with the support of DEET (Diethyltoluamide). This research is research Descriptive quantitative with a gradual revision defines the Thiagarajan development model. Data collection techniques are done by distributing questionnaires, observations, and interview. The results showed 80% of abstract animal embryology and reproduction  materials, 80% of teaching materials were less attractive, 85% were difficult to understand, 80% of images were minimal and 85% were teratologies in developing difficult animals. Analysis of the need for textbooks shows that there is no embryology and animal reproduction textbook as a result of research on developing mouse embryos with the help of DEET (Diethyltoluamide).